Representasi Perlawanan Perempuan Pada Budaya Patriarki Dalam Film Perempuan Berkalung Sorban Karya Hanung Bramantyo (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
This study analyzes how women struggle in patriarchal culture depicted in the film Perempuan Berkalung Sorban. This film was based on a novel by Abidah El Khalieqy, then this novel was adapted into a film directed by Hanung Bramantyo. The film Perempuan Berkalung Sorban was released in 2009. In this study, the film was chosen as the object of research because this film was filled with contradictions in its screening and raised the theme of gender equality in society. In this research, it is descriptive-explanative. The framing of women's resistance to patriarchal culture contained in the film Perempuan Berkalung Sorban uses the framing analysis model of Zhongdang Pan and Gerald M. Kosicki. The framing analysis model goes through four stages namely syntax, script, rhetoric, thematic. The syntactic part of this film is depicted through the figure of Anissa in fighting against patriarchal culture. The script shows patriarchal narratives of female characters in this film. The title of the film is part of the rhetoric, Anissa's struggle against injustice becomes part of the thematic. The theory chosen as a scalpel in analyzing this research is Simone De Beauvoir's existential feminist theory and Sylvia Walby's patriarchal cultural theory. Based on the results of the researcher's analysis, the film Perempuan Berkalung Sorban shows forms of women's resistance carried out by female characters in this film, including Anissa, Nyai Muthmainnah, female students. Showing the forms of patriarchal culture that are still developing in the pesantren community are carried out by Kiai Hanan, Syamsudin, several pesantren leadership figures and outside the pesantren are carried out by the general public and state institutions. The researcher concludes that Anissa and other female characters struggle to achieve an equal position with men through masculinity. Keywords: Women's resistance, patriarchal culture, the film Perempuan Berkalung Sorban, Simone De Beauvoir's existential feminism, Zhongdang Pan and Gerald M. Kosicki's framing analysis.